STUDI AGRIBISNIS PADI : FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI PADI (SUATU KASUS DI TASIKMALAYA) - Rasmikayati, Elly; Suminartika, Eti; Saefudin, Bobby Rachmat (Agros Journal of Agriculture Science, 2024)
Indonesia is one of the countries with the fourth highest rice consumption in the world. This large consumption must of course be supported by high rice production. Tasikmalaya Regency is not the area with the highest rice production in Indonesia, but this district has the potential for developing rice farming which can still be maximized. Based on this explanation, the research analyzes the factors that influence rice production in Tasikmalaya Regency using the multiple linear regression method with the help of SPSS and Microsoft Excel applications. Data was collected through a survey of 50 rice farmers in Tasikmalaya Regency using a questionnaire. The results of the analysis show that land area and fertilizer costs per season have a significant positive effect on rice production. Other factors such as farmer age, seed prices, farming experience, and dry grain prices do not partially have a significant influence on rice production. Furthermore, the regression model can be used to predict rice commodity production with 66% of the variance in Rice Production can be explained in this Regression model. Key-words: production, rice farming, regression analysis